Design of Nanocrystalline Medium-Voltage Medium-Frequency Three-Phase Transformers for Grid-Connected Applications - Gomez Jimenez, Roderick A. (2021)
This paper presents the design of a three-phase three-limb high-efficiency medium-voltage medium-frequency transformer with an integrated leakage layer using ribbon-based nanocrystalline cores for three-phase grid-connected applications. The design methodology is based on a custom-core approach developed by a series of design equations that allow the user to select a design that best fits the transformer specifications. A 150-kVA 10-kHz 5-kV-to-400-V three-phase three-limb transformer is designed to validate the proposed design method. In addition, a series of experimental characterization tests are conducted to measure the performance of the design according do thetheoretical performance.